The Potential Supply Of Plant Resources For Local Community Use In Queen Elizabeth Protected Area, Western Uganda - Bitariho, Robert; McNeilage, Alastair; Barigyira, Robert; Safari, Crispine; Neema, Robert (Institute of Tropical Forest Conservation, 2007)
Plant resources for local community use in Queen Elizabeth Protected Area (QEPA) have been designated in areas called integrated resource use zones. The integrated resource use zones of QEPA are the four islands on Lake George (Akiika, Butonga, Rwebitokye and Kankuranga) and Kigezi wildlife reserve (South Maramagambo forest). The four islands on Lake George were designated to an area of 23.2km2 for the extraction of papyrus, ambatch and phragmites while the integrated conservation area of Kigezi Wildlife reserve was designated to an area of 147km2 for the extraction of medicinal and weaving plants. We carried out a study to assess the availability of plant resources in the designated integrated resource use zones of QEPA in order to determine the plant stock and prevent the over-exploitation of the plant resources when harvesting begins. We used participatory rural appraisal (PRA) methods to interview the local fishermen, basket weavers and traditional herbalists that live adjacent the designated integrated resource use zones of QEPA. We also used subjective focused searches in the zones to scientifically identify the plant resources used by the local people and to assess whether the plant resources are available or absent in the zones. Forest surveys using transects and plots were also used in the zones to determine the abundance and distribution of plant resources used by the local people. From the interviews, 103 medicinal and 21 basket weaving plants were requested for harvest by the local people living adjacent Kigezi Wildlife Reserve. The fishermen requested for three plants of ambatch, papyrus and phragmites from Lake George islands. A comparison of the requested plant abundance using the subjective focused searches and the transect/plot methods revealed little difference between the two methods. Only 18% and 33% of the requested medicinal and basket weaving plants respectively were common, while all the three requested plants from Lake George islands were common. From the list of resource plants considered common, we further used a cut-off stem density of ≥0.1 stems/ha, ≥10 stems/ha and 40 stems/ha for trees, lianas/shrubs and vines respectively at the lower limit of 95% confidence interval as 3the recommended plants sufficiently abundant for harvest. We also recommend an annual harvest quota of the requested plants based on 1% of available plant stock in the integrated resource use zone. As such from a list of 21 weaving plants, only 8 plants were recommended for harvest. Also from a list of 103 medicinal plants, only 18 were recommended for harvest. Ambatch has not been recommended for harvest from Lake George Islands because the demand for it greatly outstrips the potential supply and it is an important food for elephants, which feed frequently in areas where ambatch grows on these islands. Papyrus and phragmites can be harvested by the fishermen of Kashaka and Kasenyi. We further recommend more studies on the harvested plants annual biomass production in order to determine their sustainable harvest quotas effectively.
Field report
Keywords: Plant Resources; Local Community; Queen Elizabeth; Protected Area